Stainless Steels - Singh, Ambrish (IntechOpen, 2022)
Stainless steel is an alloy steel that exhibits corrosion-resistant properties. Due to the presence of chromium (alloying element), a thin layer of chromium oxide is formed on the surface of stainless steel. The thickness of the layer is around 1-5 nm and protects the stainless steel from the atmosphere, keeping it safe from corrosion. The oxide layer is also known as the passive layer, as it will not react to any environmental conditions. The passive layer is self-repairing in nature. Any steel with 10.5% of chromium and 1.2% of carbon can be called stainless steel, of which there are five types: austenitic, ferritic, martensitic, duplex, and precipitation hardening. This book presents a literature review of studies on the different classes of stainless steel. It is a useful reference for those interested in corrosion studies of stainless steel in different corrosive solutions.